LEADING BY EXAMPLE: AUTOMATIC TRANSLATION OF SUBTITLES VIA EBMT. - Armstrong, Stephen; Way, Andy; Caffrey, Colm; Flanagan, Marian; Kenny, Dorothy; O'Hagan, Minako (Perspectives: Studies in Translatology, 2006)
This paper describes a project to investigate the scope of the application of Example-Based Machine Translation (EBMT) to the translation of DVD subtitles and bonus material for English-German and English-Japanese. The project focused on the development of the EBMT system and its evaluation. This was undertaken as an interdisciplinary study, combining expertise in the areas of multimedia translation, corpus linguistics and natural language processing. The main areas on which this paper focuses are subtitle corpus creation, development of the EBMT system for English-German, development of evaluation methods for MT output and an assessment of the productiveness of different data types to EBMT.